2008
DOI: 10.1080/17518420701520644
|View full text |Cite
|
Sign up to set email alerts
|

The WeeFIM [R] instrument–A paediatric measure of functional independence to predict longitudinal recovery of paediatric burn patients

Abstract: The WeeFIM can be utilized by burn centres to describe diminished functional capacity at discharge from acute care for severely burnt children. The tool can be used to track return to baseline independence after a major burn injury in a paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…[13][14][15][16] Functional/Developmental Outcomes Ten studies were identified that assessed the functional and/or developmental outcomes of pediatric burn patients. 2,4,5,[7][8][9][17][18][19][20] Two of these studies, involving the American Burn Association and Shriners Hospitals for Children, reported on the development of two questionnaires to assess function in children with burn injuries. 4,5 The first of these is a selfadministered questionnaire to monitor pediatric patients aged 5 to 18 years with burn injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] Functional/Developmental Outcomes Ten studies were identified that assessed the functional and/or developmental outcomes of pediatric burn patients. 2,4,5,[7][8][9][17][18][19][20] Two of these studies, involving the American Burn Association and Shriners Hospitals for Children, reported on the development of two questionnaires to assess function in children with burn injuries. 4,5 The first of these is a selfadministered questionnaire to monitor pediatric patients aged 5 to 18 years with burn injury.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the sensitivity of these questionnaires for patients with smaller TBSA burn injuries is not certain. Although further research is required to validate the findings of Serghiou et al, 2 the WeeFIM instrument seems a potentially useful measurement tool to assess the functional performance of children aged 6 to 16 years after major burn injury, with its brevity, ease of use, and ease of scoring making it an attractive option.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, they misinterpreted the levels of independence among the young age group (6 months-6 years) in their study. 20 Therefore, the purpose of this study was to examine the feasibility, reliability, and agreement when the WeeFIM instrument is used in children with burns who have been admitted to Dutch burn centers.…”
Section: If You're a Caregiver What Might These Findings Mean For You?mentioning
confidence: 99%
“…For this reason, the tool has demonstrated a ceiling effect when used with a child with a disability living in the community with higher levels of function. 22,23 The Wee-FIM™ measures function at the activity level of the ICF. It has been recommended that multiple instruments should be used to comprehensively measure outcomes for children with physical disabilities.…”
Section: Functional Independence Measure For Childrenmentioning
confidence: 99%